Advance of physiopathologic mechanism and treatment of melasma - Na ZHOU; Zhengfeng LIU; Jingjing TAO; Runying LIU; Bin YANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Melasma is a common chronic recurrent pigmentation disorder which tends to occur in women. It can produce an important impact on the quality of life of patients. The physiopathologic mechanism of melasma is complex. In addition to melanocytes, it also relates to vascular hyperplasia, inflammatory factors and the destruction of basement membrane. This paper reviews the pathophysiological mechanism and treatment of melasma to provide some new strategies for better treatment of melasma in the future.